(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2022)
This article provides an approach to the university research work “Ethical dimension of the professional practice of law in the province of Buenos Aires. Challenges for teaching and professional practice in the XXI century.” The topic focuses on how the teaching of the practice of law in the universities is a tool for social transformation. From the reality about how professional law practice is taught today, towards the humanistic perspective proposed by the Encyclical Letter Laudato Si and the Sustainable Development Goals (SDG Nations United). The research from a practical approach links this humanistic perspective of teaching professional practice with: sustainability, environment and professional ethics.